Sasirangan Fabric Purchase Decision Based on Product Quality, Price and Service Quality at Hafizah Sasirangan SMEs Serdang Bedagai, North Sumatra - Hartika Hartika; Abd. Rasyid Syamsuri (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study examines Sasirangan fabric purchase decisions made at Hafizah Sasirangan Micro, Small, and Medium Enterprises ((MSMEs) in Lubuk Cemara Village, Serdang Bedagai, North Sumatra based on product quality, price, and service quality. Descriptive quantitative research is the term for this kind of study. Using the saturated sample method, the study's sample consisted of 40 respondents who were Sasirangan fabric buyers at Hafizah Sasirangan SMEs. Primary data and secondary data were used in the data collection for this investigation. Multiple linear regression has been used as the data analysis method in this study. With a value of 4.950 > 2.028, the results partially demonstrate that product quality has a positive and significant impact on purchase decisions for Sasirangan fabrics. With a Tcount of 3.102 > 2.028, price has a positive and significant influence on purchasing decisions for Sasirangan fabric. The Tcount 4.642 > 2.028 shows that customer service has a positive and significant impact on purchasing decisions for Sasirangan cloth. With an Fcount value of 244.238 > 3.259, Sasirangan fabric has a positive and significant impact on purchasing decisions simultaneously on product quality, pricing, and service quality. The effect on purchase decisions is 95.3% based on the R Square value of product quality, price, and service quality, as shown by the R Square value of 0.953. Keywords: Product Quality, Price, Service Quality, Purchase Decision